Computer Simulation Feasibility for Newton’s Law Learning - Dyah Permata Sari, Wahono Widodo, Madlazim (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purposes of this research is to test the feasibility of a Computer Simulation of Motion and Force (SKGG), Computer Simulation of Action and Reaction Force (SKGAR), for learning Newton's Law. The specific objectives of the study are: 1. Describe the validity of the SKGG and SKGAR for learning Newton’s Law to improve students' understanding on the concept of motion and force. 2. Describe the practicality of the SKGG and SKGAR for learning Newton's Law. 3. Describe the effectiveness of the SKGG and SKGAR for learning Newton's Law. Data collection techniques are used to obtain materials that are relevant, accurate, and can be used appropriately according to research objectives. The data collection techniques used in this study are: (1) validation techniques; (2) observation; (3) test; and (4) questionnaire. Data analysis in this study describes the validity, effectiveness, and practicality of computer simulation prototypes. The data analysis is inductive based on the facts used to answer the problem formulation that has been formulated in the study, which emphasizes the meaning more than generalizationThe results of this study indicate that Based on the results of the analysis, discussion, and research findings, it can be concluded that the computer simulations that have been developed are valid, practical, and effective to improve understanding on the concepts of motion and force in relation. to Newton's Law.